Computational Study on the Mechanism of Cycloaddition Reactions of Bissulfonyl-1,3-butadiene with Some Alkenes - Masoumifar, Sepideh; Haghdadi, Mina; Bosra, Hassan G. (Letters in Organic Chemistry, 2020)
The cycloaddition reactions of 2,3-bis (ethylene sulfonyl)-1,3-butadiene with 2,3-dimethyl- 1,3-butadiene, cyclopentadiene, 2-methyl prop-2-enoate and ethyl vinyl ether have been theoretically studied using the DFT method at the MPWB1K/cc-pVDZ level of theory. There are two possible modes of participation in each reaction (2π and 4π electron), of which the 2π electron is preferred. The energy results indicate that formations of the [2+4] cycloadducts are favored kinetically. The stereoselectivity of the [2+4] cycloaddition reaction of 2,3-bis (ethylene sulfonyl)-1,3-butadiene with cyclopentane is the highest and the energy barrier for this process is the lowest.
Keywords: density functional theory